Factors Associated with Nursing Students’ Intention to Report Needlestick Injuries: Applying the Theory of Planned Behavior - Ditching, Nelson A.; Furatero, Angel Grace F.; Iquiña, Razilee Vania S.; Sabulao, Aira Darlyn M.; Supremo, Jason M.; Oducado, Ryan Michael Flores (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: Nursing students, like other healthcare workers, are prone to needlestick injuries. Over the years, studies have been conducted regarding needlestick injuries. However, its prevalence among Filipino nursing students’ is still not known. Also, nursing students’ intention to report needlestick injuries in the Philippines has not been explored.Purpose: The purpose of this research was to determine the factors associated with the intention to report needlestick injuries among nursing students applying the Theory of Planned Behavior.Methods: This cross-sectional study used the Needlestick Injuries Reporting Intention Scale (NIRIS) and was distributed among 233 senior nursing students in Iloilo City, Philippines. Descriptive statistics and Pearson’s correlation were utilized to analyze the data.Results: The results of the study revealed that 15% of nursing students had experienced a needlestick injury. However, only less than half (45.71%) of those who sustained needlestick injury reported the incident. Nursing students exhibited a positive attitude (M=5.41; SD=0.63) toward reporting needlestick injuries. They perceived a high social pressure (M=4.65; SD=0.46), high behavioral control (M=4.19; SD=0.45), and high intention (M=8.99; SD=1.15) in reporting needlestick injuries. Attitude (p=0.000), subjective norm (p=0.000), and perceived behavioral control (p=0.000) were significantly correlated with the intention to report needlestick injuries.Conclusion: This study supports the Theory of Planned Behavior in identifying factors influencing nursing students’ intention to report needlestick injuries.